MENUMBUHKAN KARAKTER DAN KEIMANAN SEJAK DINI: INTEGRASI PENDIDIKAN AGAMA DAN PENERAPAN MORAL PADA ANAK USIA DINI USIA 4-6 TAHUN - Dini, Hasna Aulia; Nurul Falah Qomariah; Kulsum Nur Hayati (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
The aim of this research is to find out how kindergarten students aged 4 to 6 years develop their faith and character through a combination of religious and moral teaching. This research uses a qualitative research methodology which involves direct observation and the involvement of researchers in learning activities aimed at understanding moral and religious principles. Observations, interviews with parents and teachers, and recording class activities are some of the data collection techniques used in this research. The development of children's personality and faith is greatly influenced by religious habituation through routine activities of congregational prayer, sharing and instilling morals of honesty, empathy and discipline. Children's social and emotional behavior is developing better, and children are better able to internalize religious beliefs in everyday life. Activities that are carried out regularly and involve all parties, namely teachers, parents and the community, have proven successful in cultivating a strong moral foundation and strengthening children's faith from an early age. In order to develop character and faith that is manifested in everyday life, this research emphasizes the importance of including religious and moral education as part of a comprehensive early childhood education approach. Keywords: early childhood, habituation, moral education, and character.